Restorative Justice for Children in Conflict with the Law in Narcotics Cases - Mutia Pratiwi, Gischa (International Journal of Law, Environment, and Natural Resources, 2023)
The aim of this study is to examine the implementation of restorative justice for juveniles involved in narcotics cases within the context of law enforcement. The research adopts a normative legal approach with a descriptive nature, focusing specifically on the analysis of the ambiguity within Article 82 of Law Number 11 of 2012 regarding the Juvenile Criminal Justice System. Both statutory and conceptual approaches are employed in this legal inquiry. The findings reveal that efforts to address narcotics-related offenses among juveniles are pursued through a combination of non-penal and penal policies. Non-penal measures involve preventive and repressive strategies, including counseling, awareness campaigns, distribution of informative materials such as pamphlets and billboards, engagement with traditional and religious leaders, and community guidance. In conclusion, this research underscores the necessity of integrating restorative justice principles into the handling of juvenile offenders involved in narcotics cases. It emphasizes the importance of a multifaceted approach that encompasses both preventive and punitive measures within the legal framework.